(untitled) (International Journal of Physiology, 2021)
Background : Alcohol dysregulates the innate immunity in numerous ways, making alcohol dependants more susceptible to varied forms of infections and immunological assaults. Objective : The current study on alcoholics throws light on the consequence of short term alcohol abstinence on neutrophil phagocytic power. Method : 21 subjects meeting the inclusion and exclusion criteria were enrolled for the study.Their blood samples were collected before and after a period of abstinence and studied for neutrophil phagocytic index using Candida phagocytic assay test. Result : An increase in the Mean Particle Number(MPN) of phagocytosis was observed in all the individuals after the alcohol-free period. Conclusion : The improvement in phagocytic ability of neutrophils post-abstinence provides us an insight into the ways alcohol manipulates the defense mechanism of the human body .Understanding this might help us in exploring novel ideas to circumvent the mortality and morbidity in alcoholics.